Association between alcohol consumption trajectories and clinical profiles among women and men living with HIV. (2nd January 2018) - Kelso-Chichetto, Natalie E.; Plankey, Michael; Abraham, Alison G.; Ennis, Nicole; Chen, Xinguang; Bolan, Robert; Cook, Robert L.
ABSTRACT: Background : Alcohol use is common among persons living with HIV (PLWH). It is unclear how alcohol consumption changes over time and if these changes are associated with clinical profiles. Objective : We aimed to describe the association between longitudinal patterns of alcohol consumption and the clinical profiles of PLWH. Methods : Data from the Women's Interagency HIV Study ( n = 1123 women) and Multicenter AIDS Cohort Study ( n = 597 men) from 2004 to 2013 were utilized. Group-based trajectory models were used to assess alcohol consumption patterns across 10 years. Generalized estimating equations were used to identify associations between clinical factors and alcohol consumption. All analyses were stratified by sex. Results : Four trajectories of alcohol use were identified in women and men (women: abstinent 38%, low: 25%, moderate: 30%, heavy: 7%; men: abstinent 16%, low: 69%, moderate: 9%, heavy: 5%). The Framingham Risk Score (women: adjusted odds ratio [AOR] 1.07, 95% confidence interval [CI] 1.04–1.09), years on ART (women: AOR 1.02, CI 1.00–1.05; men: AOR 1.05, CI 1.01–1.09), suboptimal ART adherence (men: AOR 1.23, CI 1.07–1.42), and unsuppressed viral load (women: AOR 1.82, CI 1.56–2.13; men: AOR 1.36, CI 1.17–1.58) were associated with increased odds for moderate drinking. The Framingham Risk Score (women: AOR 1.10, CI 1.07–1.14; men: AOR 1.12, CI 1.06–1.20), suboptimal adherence (women: AOR 1.25, CI 1.04–1.51), and unsuppressed viral load (women: AOR 1.78, CI 1.42–2.24) were associated with increased odds for heavy drinking. Conclusions : Clinicians should consider screening patients for alcohol consumption, particularly if patients have comorbid medical conditions, suboptimal antiretroviral adherence, and/or detectable viral load.